Apatinib Mesylate Inhibits the Proliferation and Metastasis of Epithelioid Malignant Peritoneal Mesothelioma In Vitro and In Vivo - Yang, Zhi-Ran; Chen, Zhi-Gao; Du, Xue-Mei; Li, Yan (Frontiers in Oncology, 2020)
Objective: Malignant peritoneal mesothelioma (MPM) is a rare malignancy with few effective molecular therapies. In this study, we evaluated the anti-tumor activity and safety of apatinib, a vascular endothelial growth factor receptor 2 inhibitor, in MPM in vitro and in vivo. Methods: We established several patient-derived xenograft (PDX) models and primary cell lines of MPM. The cell lines were used to study the effects of apatinib on proliferation, cell cycle, migration, and apoptosis by CCK8, flow cytometry, wound-healing, Transwell, DAPI staining, and caspase-3 assays, respectively. For in vivo study, apatinib was delivered by gastric gavage into PDX models, and then efficacy and toxicity were determined by experimental peritoneal cancer index (ePCI) score and pathological examinations. Results: Our results showed that apatinib significantly inhibited the proliferation and migration of MPM cells in vitro and induced cell cycle arrest. Studies on PDX models concurred that apatinib effectively suppressed subphrenic and liver invasions of nude mice. Moreover, histopathological analysis found that lymphocyte infiltration, coagulation necrosis and eosinophilic cell fragments were detected in tumor tissues after apatinib treatment. Apatinib showed no obvious effects on body mass of models and did not affect function of important organs, except for occasional focal lymphoid infiltration of liver (16.7%) and cardiac muscle (16.7%). Conclusions: We successfully established MPM PDX models and primary cell lines, and confirmed that apatinib effectively inhibited proliferation and metastasis of MPM in vitro and in vivo study.